2018
DOI: 10.3389/fpsyg.2018.00165
|View full text |Cite
|
Sign up to set email alerts
|

Tonal Symmetry Induces Fluency and Sense of Well-Formedness

Abstract: Fluency influences grammaticality judgments of visually presented strings in artificial grammar learning (AGL). Of many potential sources that engender fluency, symmetry is considered to be an important factor. However, symmetry may function differently for visual and auditory stimuli, which present computationally different problems. Thus, the current study aimed to examine whether objectively manipulating fluency by speeding up perception (i.e., manipulating the inter-stimulus interval, ISI, between each syl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Here, B HN(0, x) refers to a Bayes factor in which the predictions of H1 were modeled as a halfnormal distribution with an SD of x, where x scales the size of effect that could be expected (see Dienes, 2014). Using the tonal inversion paradigm, when testing on the same length as training, Jiang et al (2012) found an effect of 7% above a control; Li, Jiang, Guo, Yang, and Dienes (2013) found 6%, and Qiao et al (2018) found 6%. Thus, the rough size of effect expected if there is learning of different lengths by a mechanism that learnt the inversions per se is 6% above baseline.…”
Section: Writing Upmentioning
confidence: 99%
“…Here, B HN(0, x) refers to a Bayes factor in which the predictions of H1 were modeled as a halfnormal distribution with an SD of x, where x scales the size of effect that could be expected (see Dienes, 2014). Using the tonal inversion paradigm, when testing on the same length as training, Jiang et al (2012) found an effect of 7% above a control; Li, Jiang, Guo, Yang, and Dienes (2013) found 6%, and Qiao et al (2018) found 6%. Thus, the rough size of effect expected if there is learning of different lengths by a mechanism that learnt the inversions per se is 6% above baseline.…”
Section: Writing Upmentioning
confidence: 99%
“…We will explore a possible computational mechanism for learning inversions by reference to a paradigm introduced by Jiang et al (2012) (and explored further by Li, Jiang, Guo, Yang, & Dienes, 2013, Ling, Li, Qiao, Guo, & Dienes, 2016, and Qiao et al, 2018. By controlling both chunks and repetition structures, Jiang et al showed that Chinese participants could implicitly learn to discriminate lexical tonal inversions from non-inversions.…”
Section: Introductionmentioning
confidence: 99%